COMPLEX THERAPY FOR VASCULAR DISORDERS IN PATIENTS WITH SCLERODERMA SYSTEMATICA - M N Starovoitova; O V Desinova; A V Volkov (Современная ревматология)
Scleroderma systematica (SDS) is a disease in which vascular diseases underlie the pathogenesis and presented by diverse clinical manifestations. Raynaud's syndrome and digital ulceration are the most common symptom of the diseases, which influences the quality of life in patients and requires continuous drug therapy. The paper discusses the recent European guidelines for the management of this manifestation of SDS. The proposed recommendations cannot unfortunately be realized in full measure now due to the unavailability of some drugs. The authors give their clinical experience with therapy for the vascular manifestations of SDS.